Biomarkers and Preclinical Models for Adult T-Cell Leukemia-Lymphoma Treatment - Ratner, Lee (Frontiers in Microbiology, 2019)
Adult T-cell leukemia/lymphoma (ATL) is an aggressive lymphoproliferative malignancy with a very poor prognosis. Despite several recent advances, new therapeutic approaches are critical, and this will require successful preclinical studies, including studies in ATL cell culture systems and mouse models. Identification of accurate, reproducible biomarkers will be a crucial component of preclinical and clinical studies. This review summarizes the current state-of-the-art in each of these fields, and provides recommendations for future approaches. This problem is as an important unmet need in HTLV research.